Prevention of Scale Formation in Heat Exchanger Pipes by Using Magnetic Field - H. Sulaymon, Abbas; M. Al-Kyayyat, Jassim (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The possibility of using the magnetic field technique in prevention of forming scales in heat exchangers pipes usinghard water in heat transfer processes, also the studying the effective and controllable parameters on the mechanism ofscale formation.The new designed heat exchanger experimental system was used after carrying out the basic process designs of thesystem. This system was used to study the effect of the temperature (40-90 °C) and water flow rate (0.6-1.2 L/min) onthe total hardness with time as a function of precipitation of hardness salts from water and scale formation.Different magnetic field designs in the heat exchanger experimental system were used to study the effect of magneticfield design and strength (200-500 Gauss) on the total hardness with time as a function of precipitation of hardness saltsfrom water and scale formation.